Factors influencing intention to obtain the HPV vaccine and acceptability of 2-, 4- and 9-valent HPV vaccines: A study of undergraduate female health sciences students in Fujian, China. Issue 44 (16th October 2019) - Lin, Yulan; Lin, Zheng; He, Fei; Hu, Zhijian; Zimet, Gregory D.; Alias, Haridah; Wong, Li Ping
Abstract: Background: Little research has been conducted on the intention to obtain HPV vaccine now that the vaccine is approved for use in China. Acceptance of the three HPV vaccines, which differ in valency and price, has never been investigated. Methods: An online cross-sectional survey assessing female undergraduate students' intention to obtain the HPV vaccine and their acceptability of 2-, 4- and 9-valent HPV vaccines (2vHPV, 4vHPV, and 9vHPV, respectively). Results: Of a total of 997 complete responses, 55.2% reported intent to obtain the HPV vaccine. Some of the significant factors exerting influence on intent to obtain HPV vaccination were high knowledge score (OR = 1.469, 95% CI:1.087–1.987), perceived high risk of HPV infection (OR = 1.466, 95%CI:1.017–2.114), perception of no serious side effects (OR = 1.562, 95%CI:1.150–2.121), and mass media exposure to HPV vaccination information (OR = 2.196, 95%CI: 1.625–2.966). Socioeconomic status indicators did not significantly influence intent to obtain the HPV vaccine. A higher proportion of respondents were willing to pay for 2vHPV (78.6%) and 4vHPV (68.0%) compared with 9vHPV (49.3%). Socioeconomic status indicators were the strongest correlates of acceptability for all the three vaccines. Exposure to mass media reporting about HPV vaccination is the factor which exerts the most influence on acceptance of 9vHPV after socioeconomic status indicators. Conclusions: It is important to improve knowledge and health beliefs, and to establish a mass media marketing strategy to promote HPV vaccination in order to enhance HPV vaccine uptake. Undergraduate female students should be provided with detailed information about the different valency vaccine choices to help them make informed decisions about immunization.